Kekaburan Norma Terhadap Perusahaan Yang Lalai Dalam Pemberian Jaminan Keselamatan Dan Kesehatan Bagi Pekerja - Aziz, Kemas Abdul; Wardana, Dodi Jaya (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2022)
In order to improve the welfare of workers, the Government realizes Legal Certainty to provide benefits for workers with Law Number 13 of 2003 concerning Manpower. The legal basis, however, should be a foothold for the worker to acquire his rights and not be disqualified for unilateral interests. And vice versa, companies will be cautious because of their policies in legal oversight. This research is legal research using normative legal research methods. The results of the study concluded that there is no firmness from the regulations of Law Number 13 of 2003 for companies that are negligent in providing guarantees for workers.